P14.44 Survival benefit of lobectomy over gross-total resection without lobectomy in cases of glioblastoma in the noneloquent area: a retrospective study. (6th September 2019) - Roh, T; Kang, S; Hong, C; Chang, J
Abstract: BACKGROUND: Following resection of glioblastoma (GBM), microscopic remnants of the GBM tumor remaining in nearby tissue cause tumor recurrence more often than for other tumors, even after gross-total resection (GTR). Although surgical oncologists traditionally resect some of the surrounding normal tissue, whether further removal of nearby tissue may improve survival in GBM patients is unknown. In this single-center retrospective study, the authors assessed whether lobectomy confers a survival benefit over GTR without lobectomy when treating GBMs in the noneloquent area. MATERIAL AND METHODS: The authors selected 40 patients who had undergone GTR of a histopathologically diagnosed isocitrate dehydrogenase (IDH)-wild type GBM in the right frontal or temporal lobe and divided the patients into 2 groups according to whether GTR of the tumor involved lobectomy, defined as a supratotal resection (SupTR group, n = 20) or did not (GTR group, n = 20). Progression-free survival (PFS), overall survival (OS), and Karnofsky Performance Status (KPS) scores were compared between groups (p ≤ 0.05 for statistically significant differences). RESULTS: The median postoperative PFS times for each group were as follows: GTR group, 11.5 months (95% CI 8.8–14.2) and SupTR group, 30.7 months (95% CI 4.3–57.1; p = 0.007). The median postoperative OS times for each group were as follows: GTR group, 18.7 months (95% CI 14.3–23.1) and SupTR group, 44.1 months (95% CI 25.1–63.1; p = 0.040). The mean postoperative KPS scores (GTR, 76.5; SupTR, 77.5; p = 0.904) were not significantly different. In multivariate analysis, survival for the SupTR group was significantly longer than that for the GTR group in terms of both PFS (HR 0.230; 95% CI 0.090–0.583; p = 0.002) and OS (HR 0.247; 95% CI 0.086–0.704; p = 0.009). CONCLUSION: In cases of completely resectable, noneloquent area GBMs, SupTR provides superior PFS and OS without negatively impacting patient performance.